Peregrine Falcon, Falco peregrinus - New Jersey Department of Environmental Protection, Division of Fish and Wildlife, Endangered and Nongame Species Program (2004)
Fact sheet on endangered or threatened species in New Jersey, containing identification, habitat, and status and conservation information.